1986
DOI: 10.1029/jb091ib12p12249
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of sulfur in Mount Etna plume

Abstract: Aircraft measurements of sulfur compounds and trace elements including Po210 were carried out in the plume of the Mount Etna volcano, at distances 10 to 260 km from the crater. The experiment was performed in September 1983 following the large lava emission of March–August 1983. Trace elements, particularly Po210 and Si, were measured with the aim of calculating their atmospheric dilution and evaluating their outputs. This study enabled us to determine the SO2 to SO4 conversion rates to be between 2.2 × 10−6 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 22 publications
4
20
0
2
Order By: Relevance
“…Of the few other depletion rates reported for tropospheric plumes most are in agreement with this report that SO 2 depletion is negligible for typical plume sampling ages [e.g., Martin et al, 1986;Porter et al, 2002]. In contrast, there are two reports that offer considerably different k values: )99% loss per hour [Oppenheimer et al, 1998], and %97% loss per hour [Oppenheimer et al, 1998;Jaeschke et al, 1982].…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Of the few other depletion rates reported for tropospheric plumes most are in agreement with this report that SO 2 depletion is negligible for typical plume sampling ages [e.g., Martin et al, 1986;Porter et al, 2002]. In contrast, there are two reports that offer considerably different k values: )99% loss per hour [Oppenheimer et al, 1998], and %97% loss per hour [Oppenheimer et al, 1998;Jaeschke et al, 1982].…”
Section: Resultssupporting
confidence: 75%
“…However, a later survey of the same volcano (Mt. Etna) studied by Jaeschke et al [1982] found lower SO 2 loss rates (average of 7% per hour) [Martin et al, 1986]. This more recent investigation used Si and Po 210 as tracers for plume dispersion, as opposed to CO 2 in the former case.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SO 2 loss rates ranging from 10 -7 (e.g., Mount St. Helens) to 10 -3 (e.g., Soufrière Hills) s -1 have been estimated for tropospheric volcanic plumes at various altitudes (e.g., Martin et al, 1986;Oppenheimer et al, 1998;McGonigle et al, 2004). The loss rates were estimated using a number of different techniques (ground and satellite-based), including the correlation spectrometer (COSPEC), UV spectrometers, photometry, the Total Ozone Mapping Spectrometer, and filters (e.g., Martin et al, 1986;Oppenheimer et al, 1998;McGonigle et al, 2004). Each technique has advantages and disadvantages, and the results may not be comparable directly, however, this also justifies the need to determine more accurately the range in SO 2 loss rates in volcanic plumes.…”
Section: Introductionmentioning
confidence: 99%
“…ej. : Martin et al, 1986;Oppenheimer et al, 1998a;McGonigle et al, 2004;Rodríguez et al, 2008) (Fig. 29).…”
Section: Química Troposférica De Las Plumas Volcánicasunclassified